Firm size, exchange rate and exports performance: A firm level study of Pakistan's manufacturing sector - Asad Abbas; Muhammad Ramzan Sheikh; Muhammad Nauman Abbasi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Most of the countries are now focusing on changing its exports structure, concentration and direction. Among many other factors, firm-size and exchange rate are the vital factors that influence the export performance of a country. This study has attempted to investigate the effects of firm size and exchange rate on domestic and exports sales. The study has used panel data technique over 10 years data focusing 205 manufacturing firms representing fourteen different industrial sectors. Two models are specified to explore the impact of firm size and exchange rate. First model examines the effects on export sales while the second model explored the effects on domestic sales. The findings of the first model suggest positive link among firm size, exchange rate and export sales. The second model exposed positive effect of firm size on domestic sales ratio while real effective exchange rate and domestic sales ratio are found negative.
Keywords: 330; firm size; exchange rate; exports sales; domestic sales; manufacturing sector